A review on Water Resource Planning and Management with Special Reference to Groundwater using Remote Sensing and GIS Techniques - Shinde, S. P.; Barai, V. N.; Bansod, R. D.; Atre, A. A.; Gavit, B. K.; Kadam, S. A. (International Journal of Economic Plants, 2023)
Water is one of the most important natural resources and a physiological necessity to humankind. Freshwater is one of the necessities for the sustenance of life. The use and development of water resources in a sustainable manner is essential in the modern age due to the regular increase in water crises. Remote sensing and GIS techniques are powerful tools for analyzing and manipulating water resource development and management data. GIS technology provides suitable alternatives for the efficient management of large and complex databases. The most significant advantage of using Remote Sensing data for hydrological modeling and monitoring is its ability to generate information in the spatial and temporal domain. Remote sensing and GIS techniques are found efficient to minimize the time, labor, and money and make quick decisions for Sustainable water resources management. Remotely sensed data are most valuable when combined with numerical modeling, geographic information systems, and ground-based information. In short, both these techniques play a significant role in hydrology for water resources development and management. The remote sensing data helps in fairly accurate hydro geomorphological analysis and identification and delineation of land features. The review paper highlights Remote Sensing and GIS techniques and presents a brief review on the application of these two emerging techniques for groundwater resource management and development. Thus, surface investigation of groundwater has proved to be more accessible, time consistent, and cheaper using geomatics technologies.